Virusproteinexpression und Phänotypisierung der Immunantwort im zentralen Nervensystem von Seehundstaupevirusinfizierten Seehunden (Phoca vitulina) - Stimmer, Lev (Tierärztliche Hochschule, 2011)
In the literature section, a review about the classification of the morbillivirus genus as well as the host range, virus structure and replication of phocine distemper virus (PDV) is provided. Further, structure and function of virus genome and proteins as well as epidemiological and clinical aspects and pathogenesis of morbillivirus infection in marine mammals are described in this part. Special emphasis is given to PDVinduced epidemics in harbor seal populations in 1988 and 2002. Brain samples of 39 PDV-infected harbor seals, which died during distemper epidemics in 1988 (n = 16) and 2002 (n = 21) were investigated in the present study. Additionally, two brains of non-infected seals without neurological diseases served as reference material (controls). Formalin-fixed, paraffin-embedded tissue samples of the cerebrum, midbrain, cerebellum, and medulla oblongata were examined by histology. Myelin integrity and demyelination, respectively, were detected by luxol fast blue/cresylviolet (LFB-KEV) special staining. Furthermore, antibodies specific for astrocytes (GFAP), T- and B- lymphocytes (CD3 and CD79α), and antigen presenting cells (MHC-II) were used for immunohistological phenotyping of immune cells in the central nervous system. Further, lysozyme- and MAC 387-specific antibodies and the lectin BS-1 were used for the detection of macrophages/microglia. For the investigation of N-, P-, M-, F-, and H-proteins morbillivirus- specific monoclonal and polyclonal antibodies were used. Additional sequential immunohistochemical double staining procedures were performed in order to identify the predominantly infected cell type in selected animals. To detect morbillivirus N-mRNA and P-mRNA by in-situhybridization, digoxigenin-labeled CDV-specific probes were used. Polioencephalitis in the cerebral cortex was the main histopathological finding in investigated seals. Histopathological changes in the cerebral grey matter were subclassified In two lesion types: (1) lesion type I, characterized by mild gliosis without ...